Some Star related I-cordial graphs - Nicholas, T.; Maya, P. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
An I-cordial labeling of a graph G = (V, E) is an injective map f from V to * + or * ⌊ ⌋ ⌊ ⌋+ as p is even or odd, respectively be an injective mapping such that f(u) + f(v) ≠ 0 and induces an edge labeling f* : E → 0, 1 where, f * (uv) = 1 if f(u) + f(v) > 0 and f* (uv) = 0 otherwise, such that the number of edges labeled with1and the number of edges labeled with 0 differ at most by 1. If a graph has I-cordial labeling, then it is called I-cordial graph.In this paper, we prove that Bm,n, S’(Bn,n), D2(Bm,n) are I-cordial; Kn,n is I-cordial only if n is even ; Km,n is I-cordial only if m or n is even and Bn,n 2 is not I-cordial.